(untitled) (Medicine Today, 2013)
Leprosy is the most ancient bacterial disease in the history of mankind. It remains still public health problem in the countries where it is endemic. Leprosy (Hansens disease) is a chronic infectious disease which is diagnosable and curable if recognized early and treated adequately. The infectious agent of leprosy is Mycobacterium leprae which is only bacteria to infect peripheral nerves. Leprosy is characterized by a variety of abnormal immune response. It depends on the integrity of the hosts specific CMI response to the M. leprae and it may be genetically determined. Antileprotic multidrugs therapy (MDT) as recommended by WHO is now the standard and accepted method for leprosy control. Leprosy can not be completely rooted out with physicians, control offices, leprosaria and propaganda; it will disappear when the economic and cultural factors change, because leprosy is the thermometer of civilization. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14116 Medicine TODAY Vol.24(1) 2012 pp.44-47